Downregulation of miR-3568 Protects Against Ischemia/Reperfusion-Induced Cardiac Dysfunction in Rats and Apoptosis in H9C2 Cardiomyocytes Through Targeting TRIM62 - Li, Xin; Wang, Xin; Liu, Yuan-sheng; Wang, Xiao-dong; Zhou, Jian; Zhou, Hua (Frontiers in Pharmacology, 2020)
microRNA-3568 (miR-3568) has been reported to be associated with atherosclerosis. Only few data describe the expression and underlying mechanism of miR-3568 in regulating cardiac ischemia-reperfusion (I/R) injury such as apoptosis. In this study, we therefore sought to investigate the potential function of miR-3568 in simulated I/R-induced apoptosis in H9C2 cardiomyocytes and related signaling pathways involved. Flow cytometry was performed to examine the cell apoptosis. The expression of miR-3568, Survivin, Bcl-2, ERK, JNK, p38, AKT, and STAT3 was measured by western blot and Quantitative Real-time PCR. The correlation between TRIM62 and p-STAT3 was measured by Co-immunoprecipitation and ubiquitination. We found that miR-3568 expression in simulated I/R-induced H9C2 cardiomyocytes was increased in a time-dependent manner. miR-3568 mimic transfection in H9C2 cardiomyocytes significantly enhanced cell apoptosis, decreased the expression of Bcl-2 and Survivin and activated STAT3 signaling, which were reversed by miR-3568 inhibitor. The direct interaction between miR-3568 and the 3′-untranslated region (UTR) of TRIM62 mRNA was confirmed by dual-luciferase reporter assay. TRIM62 overexpression or AG490, a selective inhibitor of JAK2/STAT3 significantly, significantly inhibited I/R and miR-3568 mimic induced cell apoptosis and STAT3 activation. TRIM62 was found to interact with and induce ubiquitination of p-STAT3. The facilitating role of miR-3568 in I/R injury was also observed in our in vivo rat models. In conclusion, our study suggests that miR-3568 promotes simulated I/R-induced apoptosis in H9C2 cardiomyocytes through targeting TRIM62.